Composição físico-química, perfil de ácidos graxos e compostos bioativos de frutos e estabilidade do óleo de noz-pecã do sul do Brasil - Silva, Tamires de Oliveira Duarte da (Universidade do Vale do Rio dos Sinos, 2024)
Pecan is an oilseed known for its high content of polyunsaturated fatty acids and vitamin E. In Brazil, the cultivation and processing of this species stands out in Rio Grande do Sul, highlighting the need to improve knowledge about its composition. This study aimed to evaluate the physicochemical characteristics, fatty acid profile and bioactive compounds of different pecan cultivars, in addition to analyzing the extraction of oil by cold pressing and its oxidative stability with and without the addition of antioxidants. Fruit samples from seven cultivars were collected and subjected to analyses of color, centesimal composition, acidity, peroxide value, specific extraction coefficient, as well as the composition of fatty acids, tocopherols and phenolic compounds. The results highlighted the Elliot cultivar for its high lipid content of 74.66%. On the other hand, the Shawnee cultivar was more susceptible to oxidation, presenting high acidity and peroxide values. Elliot also stood out for its highest gammatocopherol content, while the Success cultivar had the highest delta-tocopherol content. The Shawnee, Elliot and Mohawk cultivars exhibited the highest amounts of saturated, monounsaturated and polyunsaturated fatty acids, respectively. Despite variations in the fatty acid profile among the cultivars, unsaturated fatty acids predominated, suggesting better nutritional quality, although with a higher oxidation potential. Oil samples were obtained from a blend of pecan nuts by cold pressing and stored with and without tocopherol. Physicochemical analyses over eight months revealed a predominance of oleic and linoleic fatty acids. These results provide important support for establishing quality standards and improving production processes in the Brazilian agroindustry of this promising product.
Keywords: Noz-pecã; Óleo de noz-pecã; Ácidos graxos polinsaturados; Estabilidade oxidativa; Pecan nut; Pecan oil; Polyunsaturated fatty acids; Oxidative stability; ACCNPQ::Ciências da Saúde::Nutrição